Anxiety and depression in patients with hand eczema: A population‐based study among 853 middle‐aged subjects - Koskelo, Marjut; Sinikumpu, Suvi‐Päivikki; Jokelainen, Jari; Huilaja, Laura (Contact dermatitis, 2023)
BackgroundHand eczema (HE) is a common dermatological disorder with considerable effect on the health‐related quality of life (HRQoL). The data on mental comorbidities of HE is sparse and mostly studied among selected patient groups.ObjectivesWe aimed to investigate symptoms of depression and anxiety in patients with HE in general population.MethodsStudy subjects (n = 6695) belonging to the Northern Finland Birth Cohort 1966 Study (NFBC1966) responded to an extensive health questionnaire including questions about HE. Depression and anxiety symptoms were evaluated according to the Hopkins Symptom Checklist‐25 (HSCL‐25).ResultsHaving ever suffered from HE was reported by 853 (12.8%) study subjects. Symptoms scores of depression were significantly higher among (n = 172, 20.3%) HE subjects compared with (n = 884, 15.4%) subjects without HE (Odds ratio [OR] 1.40, 95% confidence interval [CI]: 1.17–1.68, P < 0.001). Correspondingly, symptoms scores of anxiety were also more common among (n = 90, 10.6%) HE subjects than among (n = 448, 7.8%) subjects without HE (OR 1.40, 95% CI: 1.10–1.78, P = 0.007). In an adjusted model, the associations remained statistically significant (OR 1.30, 95% CI: 1.08–1.57, P = 0.007 and OR 1.34, 95% CI: 1.04–1.72, P = 0.021, respectively).ConclusionsSymptoms associated with mental health should be taken into account when managing patients with HE.